2013
DOI: 10.5455/apd.35963
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral edema associated with mirtazapine: A case report

Abstract: Mirtazapine increasing both noradrenergic and serotonergic efficiency and also having effect of decreasing anxiety is a tetracyclic antidepressant. Mirtazapine are rarely associated with peripheral edema. The mechanism of peripheral edema caused by the use of mirtazapine is unknown. In this article, we aimed to discuss a case of edema occurred during treatment of mirtazapine. In medical literature this is the fourth report of peripheral edema associated with the mirtazapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, a pretibial edema developed a day later. The edema, which began to decrease three days after the discontinuation of mirtazapine, completely disappeared within 10 day 8 . Kutscher et al reported that in a 60-year-old male patient diagnosed with hypertension, dyspnea and obesity, who was being treated with gabapentin for neuropathic pain, and with lorazepam for anxiety, began to develop peripheral edema after being medicated with mirtazapine for his depression and anxiety.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a pretibial edema developed a day later. The edema, which began to decrease three days after the discontinuation of mirtazapine, completely disappeared within 10 day 8 . Kutscher et al reported that in a 60-year-old male patient diagnosed with hypertension, dyspnea and obesity, who was being treated with gabapentin for neuropathic pain, and with lorazepam for anxiety, began to develop peripheral edema after being medicated with mirtazapine for his depression and anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Peripheral edema may occur with many systemic diseases such as liver cirrhosis, kidney diseases, congestive heart failure, and concomitant use of medications such as nonsteroid anti-inflammatory medicines, steroids, and antihypertensive medicines. There are cases of peripheral edema caused by antidepressants s u c h a s t r a n y l c y p r o m i n e , p h e n e l z i n e , i s o c a r b o x a z i d , e s c i t a l o p r a m , s e r t r a l i n e, mirtazapine, and trazodone reported in the relevant literature [6][7][8] . Although there is a case of peripheral edema related to paroxetine use in the literature, there is no peripheral edema case related to its discontinuation has been reported 9 .…”
Section: Introductionmentioning
confidence: 99%